2015
DOI: 10.1007/s12576-015-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term training camp on arterial stiffness in endurance runners

Abstract: Lack of elasticity in the central artery causes an increase in left ventricular (LV) afterload. Although regular moderate-intensity endurance exercise improves cardiovascular function, including arterial destiffening, little is known about the effect of short-term vigorous exercise on cardiovascular function (i.e., the interaction between cardiac and arterial functions). We measured arterial stiffness [via pulse wave velocity from the heart to ankle (haPWV)] and LV contractility (via systolic interval time) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Steding et al [40] reported the relationship between oxygen uptake and cardiac diastolic volume in endurance athletes. On the other hand, recent studies have reported that increased aortic stiffness is associated with reduced LV function and endurance performance [37,41]. Thus, low aortic stiffness in endurance-trained athletes might indicate endurance performance and the athletic condition.…”
Section: Endurance Performance Implicationsmentioning
confidence: 99%
“…Steding et al [40] reported the relationship between oxygen uptake and cardiac diastolic volume in endurance athletes. On the other hand, recent studies have reported that increased aortic stiffness is associated with reduced LV function and endurance performance [37,41]. Thus, low aortic stiffness in endurance-trained athletes might indicate endurance performance and the athletic condition.…”
Section: Endurance Performance Implicationsmentioning
confidence: 99%
“…We previously reported that in well-trained male collegiate endurance runners, systemic arterial stiffness increased after a 7-day intense endurance training camp (Tomoto et al, 2015 ). Since arterial stiffening promotes early return of the reflected wave from peripheral to the heart and increases aortic BP (Nichols and McDonald, 2011 ), we hypothesized that the arterial stiffening induced by intense endurance training may cause to amplify the aortic arterial pressure waveform.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, baPWV monitoring can provide an assessment of physical condition associated with sport performance for coaches and athletes in sports. Tomoto et al [28] studied highly trained male collegiate endurance runners who participated in a training camp that involved relatively higher-intensity exercise and greater training volume. They found that systemic arterial stiffness was significantly increased after the camp.…”
Section: Discussionmentioning
confidence: 99%